Immunomodulation by Ayurveda: A New Frontier in Modern Health Care (AYUSHDHARA, 2024)
Immunomodulation is described as regulation and modulation of immunity that might be achieved by reducing or enhancing the immune response depending on the intended result. Since immunomodulation can be used to treat a variety of illnesses, including cancer, infectious diseases, and autoimmune disorders. Not only does Ayurveda contain the fundamental idea of immunomodulation, but Ayurvedic specialists have been using it for centuries. Methods: The completion of this study involved consolidating information from classical Ayurvedic texts, academic research papers, guidelines, as well as searching databases such as PubMed and MedLine. Results and Discussion: Immunomodulation through Ayurveda single drugs heralds a novel and holistic approach to enhancing child health. Ayurveda, with its rich heritage of natural remedies, offers a treasure trove of single herbal drugs known for their immunomodulatory properties. Conclusion: Many of herbs have been traditionally used to bolster immunity and maintain healthy balance. Utilizing these single drugs in general care can potentially enhance the immune response in all, promoting resilience against infections and diseases. Unlike conventional pharmaceuticals, Ayurveda's natural approach aims to harmonize the body's internal environment, supporting the immune system without adverse side effects.